Energy expenditure, insulin, and VLDL-triglyceride production in humans - Lars C. Gormsen; Michael D. Jensen; Ole Schmitz; Niels Møller; Jens S. Christiansen; Søren Nielsen (Journal of Lipid Research, 2006)
Hypertriglyceridemia is considered a cardiovascular risk factor in diabetic and nondiabetic subjects. In this study, we aimed to determine potential regulators of very low density lipoprotein-triglyceride (TG) production. VLDL-TG kinetics were measured in 13 men and 12 women {body mass index [mean (range)]: 24.8 (20.2–35.6) kg/m2}. VLDL-TG production was assessed from the plasma decay of a bolus injection of ex vivo labeled VLDL particles ([1-14C]triolein-VLDL-TG). Similar VLDL-TG production (μmol/min) was found in men and women. VLDL-TG production was not significantly correlated with palmitate flux ([9,10-3H]palmitate) (r = 0.09, P = 0.67) or palmitate concentration (r = −0.29, P = 0.2) but was correlated significantly with fasting insulin concentration (r = 0.46, P < 0.05) and resting energy expenditure (REE) (r = 0.45, P < 0.05). The latter correlation improved when adjusted for sex. The best multivariate model with VLDL-TG production as the dependent variable and REE, body composition, hormones, and substrate levels as independent variables included fasting insulin (P = 0.02) and REE (P = 0.02) (r2 = 0.32, P < 0.001). We conclude that VLDL kinetics are similar in men and women and that REE and plasma insulin are significant independent predictors of VLDL-TG production. FFA availability and body fat distribution are unrelated to VLDL production. We suggest that REE plays a greater role in VLDL-TG production than previously anticipated. REE and insulin should be taken into account when VLDL-TG production comparisons between groups are made.